Context-dependent roles of B cells during intestinal helminth infection. - Aidil Zaini; Kim L Good-Jacobson; Colby Zaph (Public Library of Science (PLoS), 2021)
The current approaches to reduce the burden of chronic helminth infections in endemic areas are adequate sanitation and periodic administration of deworming drugs. Yet, resistance against some deworming drugs and reinfection can still rapidly occur even after treatment. A vaccine against helminths would be an effective solution at preventing reinfection. However, vaccines against helminth parasites have yet to be successfully developed. While T helper cells and innate lymphoid cells have been established as important components of the protective type 2 response, the roles of B cells and antibodies remain the most controversial. Here, we review the roles of B cells during intestinal helminth infection. We discuss the potential factors that contribute to the context-specific roles for B cells in protection against diverse intestinal helminth parasite species, using evidence from well-defined murine model systems. Understanding the precise roles of B cells during resistance and susceptibility to helminth infection may offer a new perspective of type 2 protective immunity.